THE CONSTRUCTIONS OF POWER: A DISCOURSE ANALYSIS ON BLACK AMERICAN WOMENAS PORTRAYED IN MAUD MARTHA AND THE HATE U GIVE - Pramono, RB. Edi; Adi, Ida Rochani; Rokhman, Muh. Arif (Lire Journal (Journal of Linguistics and Literature), 2024)
This study is an attempt to present a latent racial and gendered issue repeatedly taking place in American society as depicted by two novels produced within 70 years interval of time. Maud Martha was published in 1953 and The Hate U Give in 2017. Using critical discourse analysis and qualitative research methods, this article aims to explicate the causes of the unjust construction of Black women's power relations and how Black women cope with such unfavorable situations in such very different eras. Critical discourse analysis observes people's interactions through language because language is the basic element of life and the way truth and power are produced. In power contestation, discourse plays two opposing roles i.e., maintaining or preserving the system of dominion on one side and in another side fighting against the system of dominion. Seizing discourse means seizing power. The ongoing unjust construction of racial power relations is the major discourse that Maud Martha and Starr Carter have to live in. They exercise power producing discourses of their own as their resistance against the ongoing unfavorable major discourse. The contestation of power leads to hard mass demonstrations in The Hate U Give and a solemn understanding of living a peaceful life in Maud Martha.